Long-term results for pit-picking and flap procedures in primary pilonidal sinus disease - K. Koskinen; J. Harju; K. Hermunen (BMC Surgery, 2023)
Abstract Background Pilonidal sinus disease (PSD), a common inflammatory condition of the natal cleft causing morbidity especially in young adults, is a heterogeneous disease group with no consensus regarding its best treatment. Our aim was to report long-term results for primary PSD surgery. Methods We retrospectively studied the medical records of 146 patients who underwent primary PSD surgery between November 2010 and October 2015. Of these, 113 underwent either the mini-invasive pit-picking surgery (PSS) (n = 55) or asymmetrical excision with local flap (AELF) (n = 58); we focused on the outcomes of these two subgroups. Results PSD patients who underwent mini-invasive PPS more often succeeded with day surgery (94.5% vs 32.8%, p < 0.001), had fewer postoperative complications (9.4% vs 36.2%, p = 0.002), and had shorter sick leave (median 14 days vs 21 days, p < 0.001) than did AELF patients. Nevertheless, at the first postoperative follow-up visit, both surgery methods healed similarly (75.0% vs 76.8%, p = 0.83). Our long-term follow-up, at a median of 9.3 years (range 5.4–10.6), revealed, however, that recurrence after PPS was markedly higher than after AELF (50.9% vs 10.3%, HR 6.65, p < 0.001). Conclusions PPS, which is a mini-invasive surgical technique often performed under local anaesthesia, is suitable for primary PSD, despite the high recurrence rate in our study, bearing in mind that patient selection is an important factor to consider. Primary PSD with simple sinus formations may benefit from PPS. On the other hand, primary PSD with complex sinus formations may benefit from AELF regardless of the initial slow recovery in our study. Because PSD is a very heterogenous disease, and patients have different risk factors, it is mandatory for the surgeon to master several different surgical techniques. A classification system to aid the surgeon in selecting the right surgical technique for each patient is warranted.